Self-assembled Aza-boron-dipyrromethene for ferroptosis-boosted sonodynamic therapy - You, Changwen (2022)
The presence of apoptosis inhibition proteins renders the cancer cells resistant to apoptosis, severely compromising the antitumor efficacy of sonodynamic therapy (SDT). Here, an intelligent anticancer nanoplatform based on an Aza-boron-dipyrromethene dye (denoted as Aza-BDY) is elaborately established for ferroptosis augmented SDT through cysteine (Cys) starvation. After endocytosis by tumor cells, Aza-BDY serves as both a ferroptosis inducing agent and a sonosensitizer for tumor treatment. The specific Cys response facilitates the disruption of redox homeostasis and initiation of cellular ferroptosis. Meanwhile, the released sonosensitizer causes efficient SDT and augments ferroptosis under ultrasound irradiation. Detailed in vitro and in vivo investigations demonstrate that the synergistic effect of Cys depletion and singlet oxygen (1 O2 ) generation significantly induces cancer-cell death and suppresses tumor proliferation with a high inhibition rate of 97.5 %.